CFO narcissism and corporate digital transformation✰ - Yao, Wenyun; Ni, Mengjiao; Qian, Yuhang; Yang, Shujing; Cui, Xiaona (Elsevier, 2024)
CFO narcissism plays an essential role in the corporate digital transformation. This study empirically examines the relationship between CFO narcissism and corporate digital transformation using non-financial listed companies in the Shanghai and Shenzhen stock markets from 2010 to 2021 as a research sample. We found that CFOs' narcissistic tendencies promoted a risk-taking spirit, stronger decision-making power, and higher expectations for decision-making results, thus promoting corporate digital transformation. Narcissistic CFOs tend to seek greater power and invest in innovative projects, thereby promoting digital transformation by increasing their power and corporate innovation capabilities. Further heterogeneity tests reveal that the promoting effect of CFO narcissism on digital transformation in companies is more significant in non-state-owned, large, high-leverage enterprises, and when there is a higher level of economic policy uncertainty. Finally, the economic consequences test found that CFO narcissism further amplifies the value-added effect of firms' digital transformation on total factor productivity. This study broadens the applied research on the upper echelons theory and enriches the research on the factors influencing enterprise digital transformation. It provides a decision-making reference for companies to select and hire CFOs and empirical evidence to promote corporate digital transformation and help companies achieve high-quality development. © 2024